2016
DOI: 10.1111/bju.13624
|View full text |Cite
|
Sign up to set email alerts
|

Value of 3‐Tesla multiparametric magnetic resonance imaging and targeted biopsy for improved risk stratification in patients considered for active surveillance

Abstract: Multiparametric magnetic resonance imaging is a significant tool for predicting cancer severity reclassification on CBx among AS candidates. The reclassification rate on CBx is particularly high in the group of patients who have PI-RADS grades 4 or 5 lesions. Despite the usefulness of visual-guided biopsy, it still remains highly recommended to retrieve standard fragments during CBx in order to avoid missing significant tumours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 26 publications
1
27
0
2
Order By: Relevance
“…An initial 3502 studies underwent title and abstract screening, of which 127 studies were retrieved for full‐text review. In all, 31 studies reporting on 9480 patients (4296 with prostate cancer) met the inclusion criteria for meta‐analysis; 25 studies reported on mpMRI DTA (7000 patients, 2954 with prostate cancer), 12 studies reported on bpMRI DTA (2716 patients, 1477 with prostate cancer), and six studies directly compared mpMRI and bpMRI (2047 patients, 1063 with prostate cancer). Table provides a summary of the included studies [22,34––63], while Table provides a risk of bias summary of the included studies [22,34––63].…”
Section: Resultsmentioning
confidence: 99%
“…An initial 3502 studies underwent title and abstract screening, of which 127 studies were retrieved for full‐text review. In all, 31 studies reporting on 9480 patients (4296 with prostate cancer) met the inclusion criteria for meta‐analysis; 25 studies reported on mpMRI DTA (7000 patients, 2954 with prostate cancer), 12 studies reported on bpMRI DTA (2716 patients, 1477 with prostate cancer), and six studies directly compared mpMRI and bpMRI (2047 patients, 1063 with prostate cancer). Table provides a summary of the included studies [22,34––63], while Table provides a risk of bias summary of the included studies [22,34––63].…”
Section: Resultsmentioning
confidence: 99%
“…This is not surprising considering reports showing that a standard prostate biopsy only samples approximately 1% of prostate tissue [1416]. Studies have also shown that a clinical workup strategy, which includes prostate magnetic resonance imaging (MRI), aids the prediction of the results of confirmatory biopsy findings, however the results published so far demonstrate wide space for improvement in the use of MRI for this purpose [7; 1720]. …”
Section: Introductionmentioning
confidence: 99%
“…Different authors previously confirmed that PI-RADS score is an independent predictor of csPCa in AS candidates [14][15][16]. PI-RADS score provides additional information to existing scoring systems of PCa (i.e., both Epstein et al [17], D'Amico [18] and Cancer of the Prostate Risk Assessment: CAPRA [19]), and improves the assignment of patients to different treatments: AS vs. AT [15].…”
Section: Discussionmentioning
confidence: 91%
“…Targeted biopsies (tBx) have emerged as a useful tool to reduce standard biopsy misclassification rate of csPCa during AS [14,21,22]. Pessoa et al [14] reported a reclassification rate on tBx of 74.5 and 100%, in patients with PI-RADS score 4 and 5 lesions followed with AS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation